Decoding Terrorism: Analyzing the Dynamics of Definition in Indonesian Legal Instruments - Reza Maulana Hikam (CV. Era Digital Nusantara, 2023)
Abstract: In fighting terrorism, countries such as the Republic of Indonesia adopted legal measures and instruments to implement the policy lawfully. In the creations of such measures and instruments, the Indonesian government try to define terrorist and terrorism via legal approach. Anything that was to be considered terrorist or terrorism must fulfill the categories mentioned in the legal instruments, either government regulation or law. In the process, what defined terrorism was not just an act, even the financing of terrorism can be considered into account so that it can be brought to the court. The articles seek to elaborate the change and dynamics of defining terrorist and terrorism in Indonesian legal instruments since the first regulations about counterterrorism in 2002 until 2018. The process of making such legal instruments is met with critique and amendment that will be discussed further on the subtopics of the articles. Purpose: This article aims to elaborate the evolution, dynamics and change of the definition of terrorism with historical perspectives from 2002 to 2018. Design/Methodology/Approach: Literature review, reviewing several literatures that have related topics and selecting several parts of the book to be quoted in the articles that served as the foundation and analysis of the articles. Findings: This study shows that since the differences between Government Regulation Number 1 of 2002, Law Number 15 of 2003, Law Number 6 of 2006, Law Number 9 of 2013 and Law Number 5 of 2018 have almost the exact definition of terrorism, that was focusing on “sowing terror” into Indonesian society, but there are several additional changes each time related to what became the interest of the regime. All the aforementioned regulation for countering terrorism has derivates sanctions on those who support the acts that can be included as terrorist. These dynamics and changes from 2002 to 2018 points into one direction, that terrorism is a means to an end. Originality/Value: The article differs from the usual legal studies article because of the historical approach that was used to oversee the pattern of change in the definition of terrorism in Indonesian counterterrorism legal instruments.